2009
DOI: 10.1002/mrm.22178
|View full text |Cite
|
Sign up to set email alerts
|

T2 measurement in articular cartilage: Impact of the fitting method on accuracy and precision at low SNR

Abstract: T 2 relaxation time is a promising MRI parameter for the detection of cartilage degeneration in osteoarthritis. However, the accuracy and precision of the measured T 2 may be substantially impaired by the low signal-to-noise ratio of images available from clinical examinations. The purpose of this work was to assess the accuracy and precision of the traditional fit methods (linear least-squares regression and nonlinear fit to an exponential) and two new noise-corrected fit methods: fit to a noisecorrected expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
194
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(203 citation statements)
references
References 38 publications
6
194
2
1
Order By: Relevance
“…A P value of less than .01 was considered to indicate a significant difference. (25,26). Because only three parameters, namely short T2*, long T2*, and the short or long T2* fraction, were fitted in this bicomponent model, robust fitting could be achieved with clinically achievable signal-to-noise ratios (16).…”
Section: Discussionmentioning
confidence: 99%
“…A P value of less than .01 was considered to indicate a significant difference. (25,26). Because only three parameters, namely short T2*, long T2*, and the short or long T2* fraction, were fitted in this bicomponent model, robust fitting could be achieved with clinically achievable signal-to-noise ratios (16).…”
Section: Discussionmentioning
confidence: 99%
“…To allow noise corrected bicomponent fitting on a voxel by voxel basis, we adopted the following model (27,28,31):…”
Section: ½2mentioning
confidence: 99%
“…2, and I n is the modified Bessel function of the first kind of nth order. A recent article by Raya et al (31) showed that this noise corrected model is the most accurate and precise method of calculating T 2 , especially for low SNR images. After fitting was finished, goodness of fit statistics including the R-squared value, mean squared error, root mean squared error, and standard error were computed.…”
Section: ½2mentioning
confidence: 99%
“…There may also be little distinction in T 2 values within the spectrum of pre-radiographic to radiographic cartilage damage [34,90]. In addition to being affected by the angle at which cartilage is positioned with respect to the main magnetic field [55], T 2 values are sensitive to the type of radiofrequency coil [91], the choice of pulse sequence and sequence parameters [92], the joint position during imaging [93] and the type of equation used to fit data [94].…”
Section: T 2 Mappingmentioning
confidence: 99%